Biological Age and Second Language Acquisition (SLA) overtime : A Literature Review. - Arenas, Aitor (Journal of Literature Language and Academic Studies, 2024)
The issue of the influence of biological/chronological age on Second Language Acquisition (SLA) has been long studied in academia. This theoretical review paper addresses the evolution of this issue over the decades, specially addressing the reality of foreign language learning contexts and older adult learners, which have been studied to a lesser extent overtime. The early perspectives supported the existence of a special or critical period that would favor language learning before puberty. Since then, this theory has partially been supported in certain contexts in which learning a language at an earlier age has been found to be more advantageous. However, learning at later ages has not been found to be impossible. In general terms, the academic consensus seems to state that the Critical Period Hypothesis (CPH) would mainly be applicable to the phonological/phonetic domain. The consensus also tends to state that an adult can be a successful learner of a second language as long as certain aspects are present. For instance, by having good learning motivation/affectivity and an appropriate learning context. Moreover, adults would benefit from formal language learning classrooms because of their higher cognitive maturity and complexity. These findings suggest that older age does not seem to be an impediment for possible successful second language learning. At the same time, it is argued that learning a new language as an adult and senior can have positive effects for the learner in the cognitive and social domains, provided that the specificities of this age range are considered. Finally, new research regarding senior second language learning is deemed necessary.